A modified acrylic adhesive and its preparation method and application

By introducing isomerizable azophenyl groups into the acrylate adhesive, the molecular chains are shrinked by UV light and destroying the bonding and adhesion, the problem of difficult disassembly of components in the prior art is solved, and efficient bonding and disassembly effects are achieved.

CN119752366APending Publication Date: 2025-04-04SHENZHEN YANYI NEW MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311263685.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing acrylic adhesives are difficult to disassemble during the use of components, and the cross-linking network structure of the adhesive layer is difficult to destroy, resulting in the inability to effectively remove the adhesive force.

Method used

By adding a modified monomer containing isomerizable azophenyl groups to the acrylate, the transition from the trans structure to the cis structure of the azophenyl group under UV light conditions leads to a smaller bond length, shrinking of the molecular chain produces internal stress, and destroying the bonding and adhesion with the substrate.

Benefits of technology

The detachable bond between components is achieved, the adhesive layer is avoided, and the adhesive layer is kept simple and chemical reagents are not used, which solves the limitations of thickness and color on the detachable adhesive.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119752366A_ABST
    Figure CN119752366A_ABST
Patent Text Reader

Abstract

The present invention provides a modified acrylate adhesive and a preparation method and application thereof, belonging to the technical field of adhesives. The modified acrylate adhesive of the present invention comprises a modified acrylate, which is prepared by a first monomer containing an acrylate group and a second monomer containing an azophenyl group, and the two ends of the second monomer have a strong polar group and a double bond, respectively. An isomerizable azophenyl group is added to the acrylate, and after curing, the azophenyl group is suspended on the polymer side chain through a double bond; and the strong polar group forms hydrogen bonds and other forces with the substrate and / or filler, so that it has strong adhesion to the substrate. When exposed to UV radiation, the adhesion between the strong polar group and the substrate and / or filler will break due to the internal stress generated by the contraction of the azophenyl bond length, which solves the problem of the difficulty in disassembly of components after being bonded with acrylate in the prior art, and further solves the limitations of thickness and color on such detachable adhesives.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adhesives, and in particular relates to a modified acrylate adhesive and a preparation method and application thereof. Background Art

[0002] Acrylic adhesives are currently the most commonly used adhesive type due to their low cost and simple manufacturing process. They are widely used in thermal curing, light curing or two-component curing systems. In industries such as new energy vehicles, electronics and electrical, medical and health care, aircraft and ships, acrylic adhesives play an important role in fixing, heat conduction, insulation and other special functions for some key components. In recent years, with the requirements of green environmental protection, the recycling of adhesives and the disassembly and reuse of adhered components have become an extremely important research direction.

[0003] Existing acrylic adhesives have been widely used to fix batteries and electronic products in the power systems of new energy vehicles. During use, components will inevitably suffer from scratches or aging of the surface adhesive, causing the acrylic adhesive to lose its good bonding or protective effect on the components. When the components need to be removed for secondary bonding, the cross-linked network structure inside the acrylic adhesive cannot be destroyed by simple post-processing, and the bonding force between the components cannot be effectively removed.

[0004] The traditional method of disassembling the bonded components is to destroy the bonding layer by mechanical force, which is time-consuming and labor-intensive and can easily damage the components; another method is to add heat-expandable microspheres to the adhesive layer to destroy the bonding interface or adhesive layer, such as patents with application numbers CN201710763553.6 and CN202011488613.6, but this method cannot completely clean the bonding layer, and there is still adhesive remaining on the components; there is also a method of introducing a reversible cross-linking structure, where acrylate monomers are connected with weak coupling bonds to form a cross-linking agent, and after treatment with a reducing solution, the weak coupling bonds are broken or reorganized, such as patents with application number CN202211447283.5, but this method uses highly toxic chemicals, such as thiols, and such weak coupling bonds are not stable in the air, resulting in poor durability of the adhesive. Therefore, it is necessary to develop a modified acrylate adhesive and a preparation method thereof to avoid any of the above problems existing in the prior art. Summary of the invention

[0005] The purpose of the present invention is to provide a modified acrylate adhesive and a preparation method and application thereof. The modified acrylate adhesive of the present invention is formed by adding an isomerizable azobenzene group into acrylate, so that the azobenzene group is transformed from a trans structure to a cis structure only under UV light conditions, resulting in a decrease in bond length, shrinkage of the molecular chain and generation of internal stress, thereby destroying the bonding adhesion with a substrate, thereby solving the problem in the prior art that components are difficult to disassemble after being bonded using acrylate.

[0006] In addition, the azobenzene group of the present invention is a bifunctional azobenzene segment with photoisomerization, with a double bond at one end. After curing, the azobenzene group is suspended on the polymer side chain; the other end has a strong polar group, which can form hydrogen bonds and other forces with the substrate and / or filler, so that it has strong adhesion to the substrate. When exposed to UV, the adhesion between the end with a strong polar group and the substrate and / or filler will be broken due to the contraction of the azobenzene bond length. Therefore, even if it is thicker or has color and UV light cannot penetrate the other side (bottom), it can fall off on the first irradiated side (surface) due to cohesive force destruction, so that the deep layer is exposed and further irradiated by UV until it falls off completely, solving the limitations of thickness and color on such detachable adhesives.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a modified acrylate adhesive, which includes a modified acrylate, wherein the modified acrylate is prepared by a first monomer containing an acrylate group and a second monomer containing an azophenyl group, wherein one end of the second monomer has a strong polar group and the other end has a double bond.

[0009] Furthermore, the structural formula of the second monomer is as follows:

[0010]

[0011] Wherein, R1 is a strongly polar group; R2 is an acrylate group or a methacrylate group; m, n, x, and y are each independently an integer from 0 to 12.

[0012] Furthermore, the strong polar group includes amino, nitro, hydroxyl or carboxyl.

[0013] Furthermore, m, n, x, and y are each independently an integer from 0 to 3.

[0014] Furthermore, the raw materials of the modified acrylic adhesive include basic raw materials, and the basic raw materials, calculated by 100 parts by mass, include: 30-50 parts of the first monomer, 20-45 parts of the second monomer, 5-25 parts of the toughening resin, 0.2-5 parts of the initiator, 0.02-4 parts of the accelerator, and 0.1-0.5 parts of the stabilizer.

[0015] Furthermore, the first monomer comprises at least one of methyl methacrylate, acrylamide, acrylic acid, methyl acrylate, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, cyclohexyl acrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, ethyl methacrylate, butyl methacrylate, 2-ethylhexyl methacrylate and tetrahydrofurfuryl methacrylate.

[0016] Furthermore, the toughening resin includes at least one of chlorosulfonated polyethylene, nitrile rubber, chloroprene rubber, acrylic rubber, polyether rubber and styrene-butadiene rubber.

[0017] Furthermore, the initiator is a peroxide.

[0018] Furthermore, the accelerator includes at least one of ethylenethiourea, tetramethylthiourea, vanadium acetylacetonate, acetylacetone, triphenylphosphine, n-butyraldehyde-aniline condensate 808 and benzyldimethylamine.

[0019] Furthermore, the stabilizer includes at least one of hydroquinone, p-phenol, p-methoxyphenol, 2,6-di-tert-butyl-4-methylphenol and nitro compounds.

[0020] Furthermore, the raw materials of the modified acrylic adhesive also include auxiliary raw materials, and the auxiliary raw materials include solvents, colorants, wetting agents and fillers.

[0021] Furthermore, the bonding strength of the modified acrylate adhesive is 5 to 20 MPa. After UV irradiation treatment, the bonding strength of the modified acrylate adhesive becomes 0 MPa.

[0022] Furthermore, the modified acrylate adhesive has a thickness of 10-150 μm after curing and can be peeled off after UV irradiation treatment for 10-30 minutes.

[0023] In a second aspect, the present invention provides a method for preparing the modified acrylate adhesive, the method comprising: dispersing and mixing raw materials according to a ratio to obtain the modified acrylate adhesive.

[0024] Furthermore, the dispersion and mixing is carried out by a dispersion device, the rotation speed of the dispersion device is controlled at 1000-3000 rpm, and the dispersion time is 1-5 hours.

[0025] In a third aspect, the present invention provides an application of the modified acrylate adhesive described above, which is applied to an electrochemical device.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] 1. The modified acrylate adhesive of the present invention includes modified acrylate, which is modified by introducing a unit that can be photoisomerized by modifying an acrylate resin. Under ultraviolet light irradiation, it can spontaneously shrink to form cohesion and destroy the adhesion with the substrate. The operation is simple, the amount of acrylate resin residue is small, and no chemical reagent is used, which solves the problem that components are difficult to disassemble after being bonded with acrylate in the prior art. In addition, since the azobenzene group with photoisomerization is a bifunctional azobenzene segment with a double bond at one end, after curing, the azobenzene group is suspended on the polymer side chain; the other end has a strong polar group, which can form hydrogen bonds and other forces with the substrate and / or filler, so that it has strong adhesion with the substrate. When exposed to UV light, the adhesion between the end with a strong polar group and the substrate and / or filler will break due to the contraction of the azobenzene bond length. Therefore, even if it is thick or colored and the UV light cannot penetrate the other side (bottom), it can fall off on the first irradiated side (surface) due to cohesive failure, exposing the deep layer and further irradiated by UV until it falls off completely, thus solving the limitations of thickness and color on this type of removable adhesive.

[0028] 2. The preparation method of the modified acrylic adhesive of the present invention is relatively simple and has low cost.

[0029] 3. The modified acrylic adhesive used in the electrochemical device of the present invention is not easy to age and avoids frequent replacement. It can exist stably in the air or automobile exhaust without affecting durability. In addition, when the modified acrylic adhesive is used, the curing time required is 1-5 hours, and its thickness after curing is 10-150 μm, and the bonding strength is 5-20 MPa. When dismantling, it can be peeled off after UV irradiation for 10-30 minutes, and the bonding strength becomes 0 MPa. In particular, it can be used as a thicker coating or thicker adhesive, opaque adhesive, and dark-colored adhesive, and can also be completely peeled off after UV irradiation. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 It is a schematic diagram of biaxial tensile testing of shear strength of a material in the present invention;

[0031] Figure 2 This is a comparison chart of the modified acrylate adhesive obtained in Example 1 after curing and after UV treatment;

[0032] Figure 3This is the ultraviolet absorption spectrum of the second monomer 4-amino-4'-methacrylate azobenzene solution in Example 1. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme of the present invention is clearly and completely described below in conjunction with the embodiments. The embodiments of the present invention are implemented on the premise of the technical scheme of the present invention, and detailed implementation methods and processes are given. It should be clear to those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.

[0034] The process parameters of the unrecorded specific conditions in the embodiments of the present invention are usually carried out under normal conditions. Unless otherwise specified, the raw materials used in the present invention can all be obtained from commercially available products. In the present invention, the endpoints and any values ​​of the disclosed ranges are not limited to the precise range or value, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, between the endpoint values ​​of each range, between the endpoint values ​​of each range and a separate point value, and between separate point values, one or more new numerical ranges can be combined with each other, and these numerical ranges should be considered to be specifically disclosed in the present invention.

[0035] According to a first aspect of the present invention, a modified acrylate adhesive comprises a modified acrylate, wherein the modified acrylate is prepared by a first monomer containing an acrylate group and a second monomer containing an azophenyl group, wherein the second monomer has a strong polar group at one end and a double bond at the other end.

[0036] The modified acrylate adhesive of the present invention is formed by adding an isomerizable azobenzene group to acrylate, so that the bond length becomes shorter only under UV light conditions through the transformation of the azobenzene group from a trans structure to a cis structure, so that the molecular chain shrinks and generates internal stress, thereby destroying the bonding adhesion with the substrate, solving the problem of components being difficult to disassemble after being bonded with acrylate in the prior art. In the present invention, the azobenzene group undergoes a structural transformation between a trans and a cis structure after being irradiated with ultraviolet light, which does not cause solid-liquid transformation, but only causes an increase in internal stress, thereby causing structural destruction and peeling.

[0037] In addition, the azobenzene group of the present invention is a bifunctional azobenzene segment with photoisomerization, with a double bond at one end. After curing, the azobenzene group is suspended on the polymer side chain; the other end has a strong polar group, which can form hydrogen bonds and other forces with the substrate and / or filler, so that it has strong adhesion to the substrate. When exposed to UV, the adhesion between the end with a strong polar group and the substrate and / or filler will be broken due to the contraction of the azobenzene bond length. Therefore, even if it is thicker or has color and UV light cannot penetrate the other side (bottom), it can fall off on the first irradiated side (surface) due to cohesive force destruction, so that the deep layer is exposed and further irradiated by UV until it falls off completely, solving the limitations of thickness and color on such detachable adhesives.

[0038] In the present invention, the substrate refers to the material of the object to be bonded, such as the aluminum plate and template used for bonding, which are collectively referred to as the substrate or base plate.

[0039] As an optional embodiment of the present invention, the structural formula of the second monomer is as follows:

[0040]

[0041] Wherein, R1 is a strongly polar group; R2 is an acrylate group or a methacrylate group; m, n, x, and y are each independently an integer from 0 to 12.

[0042] As an optional embodiment of the present invention, the first monomer is typically and non-limitingly selected from at least one of methyl methacrylate, acrylamide, acrylic acid, methyl acrylate, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, cyclohexyl acrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, ethyl methacrylate, butyl methacrylate, 2-ethylhexyl methacrylate and tetrahydrofurfuryl methacrylate, etc.; preferably, methyl methacrylate and / or tetrahydrofurfuryl methacrylate, which have high adhesion to most substrates and strong applicability.

[0043] As an optional embodiment of the present invention, the strong polar group is typically, but not limitedly, selected from amino, nitro, hydroxyl or carboxyl.

[0044] In the modified acrylic adhesive of the present invention, R1 is a strongly polar group, and its main functions are: ① during curing, it forms a cross-linked network through hydrogen bonding to enhance the bonding strength; ② during UV stripping, due to the weak hydrogen bonding force, azobenzene isomerization occurs, which leads to the breaking of hydrogen bonds, the destruction of the cross-linked network, and a rapid decrease in the peeling strength.

[0045] As a preferred embodiment of the present invention, m, n, x, and y are each independently an integer from 0 to 3.

[0046] In the modified acrylic adhesive of the present invention, m, n, x, and y are selected according to actual conditions. The smaller the value, the smaller the flexibility of the modified acrylic adhesive after curing, the more brittle the cured layer, and the higher the wear resistance.

[0047] As a preferred embodiment of the present invention, the second monomer is p-nitroacrylic acid azobenzene or 4-amino-4'-methacrylate azobenzene.

[0048] In the above technical solution, the amino and nitro groups have high polarity and can form strong hydrogen bonds or ionic bonds within the system, which is conducive to bonding; and the industrialization of its monomers is relatively mature, easy to obtain, and has stable performance.

[0049] As an optional embodiment of the present invention, the raw materials of the modified acrylate adhesive include basic raw materials, and the basic raw materials include, by mass parts, 30-50 parts (e.g., 31 parts, 33 parts, 35 parts, 37 parts, 39 parts, 41 parts, 43 parts, 45 parts, 47 parts, 49 parts) of the first monomer, 20-45 parts (e.g., 21 parts, 23 parts, 25 parts, 27 parts, 29 parts, 31 parts, 33 parts, 35 parts, 37 parts, 39 parts, 41 parts, 43 parts) of the second monomer, 5-25 parts (e.g., 6 parts, 8 parts, 10 parts, 12 parts, 14 parts, 16 parts, 18 parts, 20 parts, 22 parts) of the toughening resin. parts, 24 parts), initiator 0.2-5 parts (for example 0.5 parts, 0.7 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 4.7 parts, 4.9 parts), accelerator 0.02-4 parts (for example 0.05 parts, 0.1 parts, 0.5 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 3.7 parts, 3.9 parts), stabilizer 0.1-0.5 parts (for example 0.11 parts, 0.13 parts, 0.15 parts, 0.2 parts, 0.25 parts, 0.3 parts, 0.35 parts, 0.4 parts, 0.45 parts, 0.47 parts, 0.49 parts).

[0050] In the above technical scheme, after the raw material is coated, the initiator in the modified acrylate adhesive raw material can decompose under certain conditions to produce free radicals to initiate the polymerization of monomers and resins, so that the modified acrylate adhesive is cured on the surface of the substrate to form adhesion; and the toughening resin can have different functional groups, which can form a force with different substrate surfaces in a targeted manner, thereby bonding to the substrate; at the same time, the structure of the resin will also affect the hardness, wear resistance and weather resistance of the adhesive. Accelerators and stabilizers make the modified acrylate adhesive system more stable, preventing problems such as poor wettability and sagging during use and construction.

[0051] As an optional embodiment of the present invention, the raw materials of the modified acrylic adhesive further include auxiliary raw materials, and the auxiliary raw materials include solvents, colorants, wetting agents, dispersants and fillers.

[0052] In the above technical solution, auxiliary raw materials are added according to the needs of use, and may or may not be added. Among them, the use of colorants can make the modified acrylic adhesive adapt to the color of the components to be used, so that the two colors are the same or different; other additives such as wetting agents, dispersants, etc. make the modified acrylic adhesive system more stable, preventing problems such as poor wettability and sagging during the construction process. The use of fillers, on the one hand, improves the strength of the adhesive, and on the other hand, the amino groups, nitro groups, etc. on the fillers and azobenzene units are easy to form hydrogen bond cross-linked structures, which are more conducive to peeling by ultraviolet light.

[0053] As an optional embodiment of the present invention, the toughening resin is typically, but not limitedly, selected from at least one of chlorosulfonated polyethylene, nitrile rubber, chloroprene rubber, acrylic rubber, polyether rubber and styrene-butadiene rubber (SBR).

[0054] As an optional embodiment of the present invention, the initiator is a peroxide; the peroxide is typically, but not limitedly, selected from benzoyl peroxide (BPO), tert-butyl hydroperoxide (BHP), cumene hydroperoxide (CHP), dicumyl peroxide, and the like.

[0055] As a preferred embodiment of the present invention, the peroxide is CHP or BPO, which can be used as a highly efficient initiator with stable performance.

[0056] As an optional embodiment of the present invention, the accelerator is typically, but not limitedly, selected from at least one of ethylenethiourea (NA-22), tetramethylthiourea, vanadium acetylacetonate, acetylacetone, triphenylphosphine, n-butyraldehyde-aniline condensate 808 and benzyldimethylamine.

[0057] As a preferred embodiment of the present invention, the accelerator is NA-22 or tetramethylthiourea, which has stable performance and good use effect.

[0058] As an optional embodiment of the present invention, the stabilizer is typically, but not limitedly, selected from at least one of hydroquinone, p-phenol, p-methoxyphenol, 2,6-di-tert-butyl-4-methylphenol (264 (BHT)) and nitro compounds.

[0059] As a preferred embodiment of the present invention, the stabilizer is hydroquinone, which has stable performance.

[0060] As an optional embodiment of the present invention, the bonding strength of the modified acrylate adhesive is 5 to 20 MPa (for example, 6 MPa, 8 MPa, 10 MPa, 12 MPa, 14 MPa, 16 MPa, 18 MPa). After UV irradiation treatment, the bonding strength of the modified acrylate adhesive becomes 0 MPa.

[0061] As an optional embodiment of the present invention, the thickness of the modified acrylate adhesive after curing is 10-150μm (for example, 20μm, 40μm, 60μm, 80μm, 100μm, 120μm, 140μm), and it can be peeled off after UV irradiation treatment for 10-30min (for example, 12min, 14min, 16min, 18min, 20min, 22min, 24min, 26min, 28min).

[0062] According to a second aspect of the present invention, a method for preparing the modified acrylate adhesive is provided, the method comprising: dispersing and mixing raw materials according to a proportion to obtain the modified acrylate adhesive.

[0063] As an optional embodiment of the present invention, dispersion mixing is carried out by a dispersion device, and the rotation speed of the dispersion device is controlled at 1000-3000rpm (for example, 1200rpm, 1400rpm, 1600rpm, 1800rpm, 2000rpm, 2200rpm, 2400rpm, 2600rpm, 2800rpm), and the dispersion time is 1-5h (for example, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h).

[0064] In the above technical solution, the dispersing device can be a disperser or a stirrer, or other equipment with dispersing and stirring functions. Controlling the speed and time of the dispersing device within the above range can ensure the dispersing effect while improving the preparation efficiency.

[0065] According to a third aspect of the present invention, a use of the above-mentioned modified acrylate adhesive.

[0066] Specifically, an electrochemical device includes the modified acrylate adhesive. The modified acrylate adhesive can be used as a coating material or as an adhesive material. The electrochemical device can be a lithium-ion battery structural part, an automobile fuel pipeline system, a battery cell, a battery pack management system, etc. The modified acrylate adhesive is used to fix the structural part, the battery pack, etc.

[0067] When the modified acrylic adhesive of the present invention is used as a coating material or an adhesive material, it is detachable, and its curing process is the same, but there are some differences in its disassembly and shedding, as follows: when it is disassembled as a coating material, UV light can be irradiated from the top of the coating so that the coating can be gradually detached from top to bottom; when it is used as a single-sided curing adhesive, its disassembly method can be the same as that of the coating material, irradiating and shedding from the upper exposed surface, or irradiating and shedding from other exposed surfaces; when it is disassembled as a double-sided curing adhesive, if at least one of the bonded substrates is transparent, its disassembly method is to irradiate and shedding from the exposed surface of the transparent part or other exposed surfaces. In addition, due to the special design of the modified acrylic adhesive of the present invention, it can also be used as a curing adhesive with low transparency or high thickness. After UV irradiation, the adhesive on the surface is destroyed and shedding due to cohesive force, and the deep adhesive is exposed and can be further irradiated and detached by UV until the adhesive layer is completely detached.

[0068] When the modified acrylic adhesive of the present invention is used, the curing time required is 1-5 hours, the thickness after curing is 10-150 μm, the bonding strength is 5-20 MPa, and when removed, it can be peeled off after UV irradiation treatment for 10-30 minutes, and the bonding strength becomes 0 MPa.

[0069] The present invention is further described in detail below with reference to specific embodiments and comparative examples.

[0070] Example 1

[0071] 40 parts of methyl methacrylate, 35 parts of 4-amino-4'-methacrylate azobenzene, 20 parts of SBR, 0.7 parts of isopropylbenzene hydroperoxide, 4 parts of NA-22, and 0.3 parts of hydroquinone were weighed, dispersed and mixed by a disperser, and dispersed for 3 hours at a disperser speed of 2000 rpm to obtain a modified acrylic adhesive.

[0072] Among them, the structural formula of 4-amino-4'-methacrylate azobenzene is as follows:

[0073]

[0074] Embodiment 2-5

[0075] The difference from Example 1 is that the types, proportions and dispersion processes of the raw material components used in the preparation are changed, as shown in Table 1, and the rest of the settings are the same as in Example 1.

[0076] Table 1

[0077]

[0078]

[0079] Among them, the structural formula of azobenzene p-nitroacrylate is as follows:

[0080]

[0081] Examples 6-12

[0082] The difference from Example 1 is that the type of the second monomer is different, as shown in Table 2, and the rest of the settings are the same as Example 1.

[0083] Table 2

[0084]

[0085]

[0086] Examples 15-18

[0087] The difference from Example 1 is that the number of the second monomer is different, as shown in Table 3, and the rest of the settings are the same as in Example 1.

[0088] Table 3

[0089]

[0090] Embodiment 19

[0091] The difference from Example 1 is that the raw material components contain an auxiliary raw material colorant aniline black during preparation, and the specific preparation is as follows:

[0092] 40 parts of methyl methacrylate, 35 parts of 4-amino-4'-methacrylate azobenzene, 20 parts of SBR, 0.7 parts of isopropylbenzene hydroperoxide, 4 parts of NA-22, 0.3 parts of hydroquinone, and 2 parts of aniline black were weighed, dispersed and mixed by a disperser, and dispersed for 3 hours at a disperser speed of 2000 rpm to obtain a modified acrylic adhesive.

[0093] Embodiment 20

[0094] The difference from Example 19 is that phthalocyanine green G is used as the colorant, and the other settings are the same as those of Example 19.

[0095] Embodiment 21

[0096] The difference from Example 19 is that quinacridone violet is used as the colorant, and the other settings are the same as those of Example 19.

[0097] Embodiment 22

[0098] The difference from Example 1 is that the raw material components contain filler titanium dioxide during preparation, and the specific preparation is as follows:

[0099] 40 parts of methyl methacrylate, 35 parts of 4-amino-4'-methacrylate azobenzene, 20 parts of SBR, 0.7 parts of isopropylbenzene hydroperoxide, 4 parts of NA-22, 0.3 parts of hydroquinone, and 5 parts of titanium dioxide were weighed and dispersed and mixed by a disperser at a speed of 2000 rpm for 3 hours to obtain a modified acrylic adhesive.

[0100] Embodiment 23

[0101] The difference from Example 22 is that aluminum oxide is used as the filler, and the other settings are the same as those of Example 22.

[0102] Embodiment 24

[0103] The difference from Example 22 is that natural graphite is used as the filler, and the other settings are the same as those of Example 22.

[0104] Examples 25-27

[0105] The difference from Example 1 is that the type of the first monomer is different, as shown in Table 4, and the rest of the settings are the same as Example 1.

[0106] Table 4

[0107] project The first monomer type Embodiment 25 2-Ethylhexyl acrylate Embodiment 26 Acrylamide Embodiment 27 Methyl acrylate

[0108] Comparative Example 1

[0109] The only difference from Example 1 is that the second monomer is not included, and the rest of the configuration is the same as that of Example 1.

[0110] Comparative Examples 2-8

[0111] The difference from Example 1 is that the second monomer structure is different, as shown in Table 5, and the rest of the settings are the same as Example 1.

[0112] Table 5

[0113]

[0114] Tests and Results

[0115] The modified acrylate adhesives obtained in Examples 1-27 and Comparative Examples 1-8 were used as samples to test the viscosity before and after ultraviolet light exposure. The test method is as follows:

[0116] After weighing the sample, spread it on a substrate to make it bonded to the substrate, press another substrate onto the spread sample and compact it, so that the sample is bonded to the surfaces of the two substrates, and the bonding area of ​​the two substrates is 10mm*120mm. Then cure it at room temperature for 3 hours, and use a vernier caliper to measure the thickness of the cured adhesive after curing. Specifically, measure the thickness of the substrate before and after applying the sample. The thickness of the substrate before coating is h0, and the thickness of the substrate after coating and curing is h1. The thickness of the cured sample is h2=h1-h0.

[0117] After the thickness measurement, a portion of the samples were fixed with two substrates by the tensile machine fixture, and the shear strength (initial bonding strength) was tested at a speed of 5 mm / s in both directions. Figure 1 shown.

[0118] Another part of the samples were irradiated with 365nm ultraviolet light (power 8500W) to test the adhesive shedding. When the bonding strength became 0MPa after UV treatment, the UV treatment time was recorded. After a certain period of UV treatment, the bonding strength value after UV treatment was tested. The specific results are shown in Table 6:

[0119] Table 6

[0120]

[0121]

[0122] It can be seen from the test data in Table 6 that after use, the modified acrylate adhesives obtained in Examples 1-14, 16-17, and 19-27 of the present invention bond and solidify between substrates, and the thickness after curing is 10-150μm, the initial bonding strength is not less than 10MPa, and the maximum can reach 20MPa, and after irradiation with ultraviolet light, the bonding strength between them and the substrate can be reduced to 0MPa. Since the modified acrylate adhesive obtained in Example 15 has a small content of the second monomer, after UV treatment, the internal stress is insufficient, and the bonding strength is greatly reduced, but it does not reach the level of complete automatic falling off. Since the modified acrylate adhesive obtained in Example 18 has a large content of the second monomer, the proportion of the first monomer content is reduced, resulting in a lower initial bonding strength, but the UV treatment time is greatly shortened during disassembly. Among them, the macroscopic morphology of the modified acrylate adhesive obtained in Example 1 after curing (before ultraviolet light irradiation) and after UV treatment (after ultraviolet light irradiation begins to fall off) is as follows. Figure 2 As shown. Figure 2 It can be seen that the surface of the adhesive is smooth after curing, but the surface adhesive layer is seriously damaged after UV treatment. It can be seen that the modified acrylic adhesive obtained in the embodiment of the present invention has good adhesion and is easy to fall off and disassemble, and can be used as a detachable adhesive. When used, the thickness and color of the adhesive are not limited.

[0123] By comparing the test data of Example 1 with Comparative Examples 1-8, it can be seen that the modified acrylate adhesive obtained in Example 1 of the present invention can be bonded and treated with UV light, and its bonding strength can be changed to 0MPa, while the bonding strength of Comparative Example 1 without the second monomer and Comparative Example 2 containing the second monomer but not containing polar groups and double bonds after UV irradiation remains unchanged even when the irradiation time is as long as 30 minutes. In Comparative Examples 3-8, although the second monomer is contained, and the second monomer contains one of the polar groups or double bonds, the bonding strength is not completely 0MPa after 30 minutes of UV irradiation. It can be seen that the simultaneous presence of the second monomer and its strong polar groups and double bonds can make the modified acrylate adhesive fall off well after UV irradiation. This should be that when the modified acrylate used in the modified acrylate adhesive is cured, the double bond causes the azobenzene group to hang on the polymer side chain, and the strong polar group forms hydrogen bonds and other forces with the substrate, resulting in strong adhesion between the modified acrylate and the substrate. After ultraviolet irradiation, the azobenzene group undergoes a transformation from a trans structure to a cis structure, resulting in a smaller bond length, and the molecular chain of the modified acrylate shrinks to generate internal stress. The adhesion between the strong polar group and the substrate is destroyed, and the bonding strength between the modified acrylate adhesive and the substrate becomes 0MPa, and the modified acrylate adhesive automatically falls off from the substrate.

[0124] Furthermore, the second monomer 4-amino-4'-methacrylate azobenzene solution in Example 1 was subjected to ultraviolet irradiation for different time periods, and the ultraviolet absorption spectrum was as shown in FIG. Figure 3 As shown in the figure, the ultraviolet absorption curve of the second monomer in THFA has an obvious absorption peak at 365nm, and as the ultraviolet light irradiation time increases, the absorption peak at 365nm weakens, and a new absorption peak appears at 451nm, indicating that ultraviolet light causes the azobenzene monomer to undergo isomerization transformation. It can be seen that the modified acrylate adhesive obtained in the embodiment of the present invention only needs to be irradiated with ultraviolet light for a sufficient time after use as an adhesive to achieve complete shedding.

[0125] By comparing the test data of Example 1 and Examples 19-21, it can be seen that even if a colorant is used in the modified acrylic adhesive, its bonding strength can still be reduced to 0 MPa after UV ultraviolet irradiation treatment. However, with the use of colorants, the darker the color of the modified acrylic adhesive, the longer the UV treatment irradiation time is used when disassembling after bonding. Since dark colors have a light absorption effect, the UV light efficiency is greatly reduced, and the time required is longer.

[0126] The above is only a specific implementation of the present invention, but the protection scope of the present invention is not limited thereto. The above specific examples are used to illustrate the present invention, which is only used to help understand the present invention and is not used to limit the present invention. A person skilled in the art of the present invention can also make several simple deductions, deformations or substitutions based on the concept of the present invention. These deductions, deformations or substitutions also fall within the scope of the claims of the present invention.

Claims

1. A modified acrylic adhesive, characterized in that: The modified acrylate adhesive comprises modified acrylate, which is prepared by a first monomer containing an acrylate group and a second monomer containing an azobenzene group. The second monomer has two ends, one end having a strong polar group and the other end having a double bond.

2. The modified acrylate adhesive according to claim 1, characterized in that: The structural formula of the second monomer is as follows: Wherein, R1 is a strongly polar group; R2 is an acrylate group or a methacrylate group; m, n, x, and y are each independently an integer from 0 to 12.

3. The modified acrylate adhesive according to claim 2, characterized in that: The strong polar groups include amino, nitro, hydroxyl or carboxyl groups; And / or, m, n, x, y are each independently an integer from 0 to 3.

4. The modified acrylate adhesive according to any one of claims 1 to 3, characterized in that: The raw materials of the modified acrylic adhesive include basic raw materials, which include, by weight, 30-50 parts of a first monomer, 20-45 parts of a second monomer, 5-25 parts of a toughening resin, 0.2-5 parts of an initiator, 0.02-4 parts of a accelerator, and 0.1-0.5 parts of a stabilizer. And / or, the raw materials of the modified acrylic adhesive further include auxiliary raw materials, and the auxiliary raw materials include solvents, colorants, wetting agents and fillers.

5. The modified acrylic adhesive according to claim 4, characterized in that: The first monomer comprises at least one of methyl methacrylate, acrylamide, acrylic acid, methyl acrylate, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, cyclohexyl acrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, ethyl methacrylate, butyl methacrylate, 2-ethylhexyl methacrylate and tetrahydrofurfuryl methacrylate; and / or, the toughening resin comprises at least one of chlorosulfonated polyethylene, nitrile rubber, chloroprene rubber, acrylic rubber, polyether rubber and styrene-butadiene rubber; And / or, the initiator is a peroxide; and / or, the accelerator comprises at least one of ethylenethiourea, tetramethylthiourea, vanadium acetylacetonate, acetylacetone, triphenylphosphine, n-butyraldehyde-aniline condensate 808 and benzyldimethylamine; And / or, the stabilizer includes at least one of hydroquinone, p-phenol, p-methoxyphenol, 2,6-di-tert-butyl-4-methylphenol and a nitro compound.

6. The modified acrylate adhesive according to claim 4, characterized in that: The bonding strength of the modified acrylic ester adhesive is 5 to 20 MPa. After UV irradiation treatment, the bonding strength of the modified acrylic ester adhesive becomes 0 MPa.

7. The modified acrylic adhesive according to claim 6, characterized in that: The modified acrylate adhesive has a thickness of 10-150 μm after curing and can be peeled off after UV irradiation treatment for 10-30 minutes.

8. A method for preparing the modified acrylate adhesive according to any one of claims 1 to 7, characterized in that: The preparation method comprises: dispersing and mixing raw materials according to a proportion to obtain the modified acrylate adhesive.

9. The preparation method according to claim 8, characterized in that: The dispersion and mixing are carried out by a dispersion device, the rotation speed of the dispersion device is controlled at 1000-3000 rpm, and the dispersion time is 1-5 hours.

10. An electrochemical device, characterized in that: The electrochemical device comprises the modified acrylate adhesive as described in any one of claims 1 to 7 or the modified acrylate adhesive prepared by the preparation method as described in claim 8 or claim 9.

Citation Information

Patent Citations

  • Reworkable structural adhesives

    CN107325776B

  • Detachable bi-component polyurethane adhesive, preparation method thereof and detachable structural member

    CN113025259A

  • Detachable acrylate adhesive, preparation method thereof and detachable structural member

    CN115725256A